Pengembangan Media Activity Book Digital Berbasis Gamifikasi untuk Meningkatkan Kemampuan Numerasi pada Materi Operasi Hitung Perkalian Siswa Kelas III Sekolah Dasar - Veradia Prahesti Putri Amalia; Via Yustitia; Prayogo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
he low numeracy achievement of elementary school students in Indonesia indicates the need for innovative and interactive learning media to support mathematics learning, particularly in multiplication operations. This study aimed to develop a gamification-based digital activity book to improve numeracy skills in multiplication operations for third-grade elementary school students, determine its feasibility, and evaluate its practicality in learning activities. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were third-grade elementary school students and teachers, while the object of the study was a gamification-based digital activity book. Data were collected through expert validation sheets, response questionnaires, and numeracy tests. The results showed that the developed media obtained a feasibility score of 92% from media experts and 90% from material experts, both categorized as highly feasible. Furthermore, the implementation of the media improved students’ numeracy skills, as indicated by the increase in the average score from 67 on the pre-test to 87.8 on the post-test, with an average N-Gain score of 0.6135 in the moderate category. These findings indicate that the gamification-based digital activity book is feasible and effective for supporting mathematics learning and improving numeracy skills in multiplication operations among elementary school students.